Toxicity Test of Ehanol Extract 96% Malayan Mistletoe Leaf (Dendrophthoe pentandra) from Various Regions in Indonesia Against Vero Cells - Muti'ah, Roihatul; Z.A, Burhan Ma'arif; Bhagawan, Weka Sidha; Amalia, Olden Mayazzaka (Proceedings of the International Conference on Green Technology, 2017)
Different types of benalu can be found in Indonesia, one of benalu that has anticancer potency is benalu mangga ( Dendrophthoe pentandra ). This study aims to determine the difference of toxicity of ethanol extract 96% Dendrophthoe pentandra leaf from Kediri, East Java; Pekalongan, Central Java; Gunung Batin Baru, Lampung and Selor Hilir, Kaltara towards normal cell line (vero). Selection of the five regions based on the elevation where the plant grows. Ultrasonic extraction is performed to separate the active compound of Dendrophthoe pentandra leaf. The solvent used in the extraction is 96% ethanol. Each extract tested its toxicity using vero cell done by MTT method (microculture tetrazolium salt). The living cells form crystals of purple formazan and absorbance readings are performed using ELISA reader to determine the percentage of living cells. The results obtained from this research are LC 50 values from East Java, Central Java, Sumatra and Kalimantan respectively 26.61; 1583.75; 4845.32 and 798.28 μg / ml. The data analysis conducted by using one-way ANOVA showed that toxicity levels between regions have a significant difference.